ANALISIS USAHATANI PADI SAWAH PADA IRIGASI DESA DI KECAMATAN PURBOLINGGO KABUPATEN LAMPUNG TIMUR - Eny Ivans; Wan Abbas Zakaria; Helvi Yanfika (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2013)
Village irrigation is an alternative irrigation technology to complement the technical limitations of irrigation.  The purpose of village irrigation development is to increase the availability of water which can support the growth of rice plants so that the factors of production are efficiently used.  This study aimed to determine the factors that influence production, productivity levels, and farm income in irrigated rice village.  The study was done in Tanjung Kesuma village, Purbolinggo District, East Lampung regency by a survey method.  The number of 40 farmers of this research samples was drawn randomly.  The research was conducted in irrigated farm village, at the season of gadu that was occured in April until September 2012.  The factors that affected the production were analized by Cob-Douglas function.  Farming analysis was used to determine the level of farm productivity and farm income.  The results showed that the affecting factors of paddy production were land, seeds, urea, organic fertilizer, and labor.  The paddy farming in irrigated fields paddy villages during gadu growing season in 2012 was profitable.  The average productivity and farm income were 1.9 tons/ha and Rp3,387,325.89 with the R/C ratio of 2.17. Keywords : farming, income, productivity, rice, irrigated farm